Analysis of the Effects of Macroeconomic Variables on Zakat Fund Revenues in Indonesia for the 2020-2024 Period - Hakim, Fajar Arif Rahman; Widiyanti, Dwi Retno (Islamic Economics and finance in Focus, 2025)
This study aims to analyze the effect of macroeconomic variables on zakat revenue in Indonesia for the period 2020-2024. The independent variables studied include inflation, money supply (MS), industrial production index (IPI), and BI Rate as factors that potentially affect zakat revenue in Indonesia. This study uses a quantitative approach with the Vector Error Correction Model (VECM) analysis method. The data used in this study is time series data for the 2020-2024 period. The results of the analysis show that the inflation variable has no significant effect on zakat revenue in either the short or long term. Conversely, the JUB variable has a significant negative effect and the IPI has a significant positive effect on zakat revenue, both in the short and long term. Meanwhile, the BI Rate does not show a significant effect. This study provides several important implications for policymakers and zakat administrators to be more sensitive to macroeconomic conditions in an effort to improve the stability and optimization of zakat revenue in Indonesia.